CFD-DEM simulation of air-blown gasification of biomass in a bubbling fluidized bed gasifier: Effects of equivalence ratio and fluidization number. (15th March 2021) - Hwang, In Sik; Sohn, Jungho; Lee, Uen Do; Hwang, Jungho
Abstract: In this study, air-blown gasification of biomass in a bubbling fluidized bed (BFB) gasifier was numerically investigated. A discrete element model coupled with computational fluid dynamics (CFD-DEM), in which gas is considered as continuum and particle is considered as discrete phase, was employed. The flow characteristics of the BFB were discussed and compared with the reported experimental data. Then, the gasification performance of the BFB was discussed for cases with varying fluidization number (FN) values at a constant equivalence ratio (ER). In a parametric study, calculations were performed for various FN values, and the ER value was fixed as 0.27. The formation of CO2 commenced inside the fluidized bed region for FN values exceeding 3.6. When the FN value increased, slight decreases were observed in the CO and H2 concentrations as well as CCE. Thus, an increase in FN beyond a certain value was not recommended. Another parametric study was performed for various combinations of FN & ER values. The CGE increased for FN & ER values between 2.49 & 0.21 and 3.56 & 0.3, whereas it decreased for FN & ER values exceeding 3.56 & 0.3. Therefore, the optimum FN & ER values were considered as 3.56 & 0.3. Highlights: Air-blown gasification of biomass in a bubbling fluidized bed (BFB) gasifier is numerically investigated. The flow and characteristics of the BFB are discussed and compared with the reported experimental data. An increase in fluidized number (FN) a certain value is not recommended. An optimum combination of fluidized number (FN) and equivalence ratio (ER) exists at a constant biomass-feeding rate.